2022
DOI: 10.3390/educsci12090607
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Class Analysis of University Lecturers’ Switch to Online Teaching during the First COVID-19 Lockdown: The Role of Educational Technology, Self-Efficacy, and Institutional Support

Abstract: The switch to emergency remote teaching (ERT) due to the first COVID-19 lockdown demanded a lot from university lecturers yet did not pose the same challenge to all of them. This study sought to explain differences among lecturers (n = 796) from universities in France, Germany, Switzerland, and the UK in their use of educational technology for teaching, institutional support, and personal factors. Guided by the Social Cognitive Theory (SCT), lecturers’ behavior (educational technology use), environment (instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…Fifteen empirical articles that examined teachers’ digital competence across the ERT period were included for review in this study. The 15 studies included 9 high-response surveys of teachers (ranging from 50 to 1000 respondents) drawing on interdisciplinary pools of teachers (Bartolic et al, 2021 ; Damşa et al, 2021 ; Kaqinari et al, 2022 ; Mishra et al, 2020 ; Myyry et al, 2022 ; Scherer et al, 2021 ; Shrestha et al, 2022 ; Väljataga et al, 2020 ; Watermeyer et al, 2021 ) and 6 descriptive case studies (Dalipi et al, 2022 ; Gao & Zhang, 2020 ; Moustakas & Robrade, 2022 ; Müller et al, 2021 ; Oliveira et al, 2021 ; Scull et al, 2020 ). Three major themes were constructed through an analysis of the findings presented in the literature reviewed: technologies, preparedness, and experience.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen empirical articles that examined teachers’ digital competence across the ERT period were included for review in this study. The 15 studies included 9 high-response surveys of teachers (ranging from 50 to 1000 respondents) drawing on interdisciplinary pools of teachers (Bartolic et al, 2021 ; Damşa et al, 2021 ; Kaqinari et al, 2022 ; Mishra et al, 2020 ; Myyry et al, 2022 ; Scherer et al, 2021 ; Shrestha et al, 2022 ; Väljataga et al, 2020 ; Watermeyer et al, 2021 ) and 6 descriptive case studies (Dalipi et al, 2022 ; Gao & Zhang, 2020 ; Moustakas & Robrade, 2022 ; Müller et al, 2021 ; Oliveira et al, 2021 ; Scull et al, 2020 ). Three major themes were constructed through an analysis of the findings presented in the literature reviewed: technologies, preparedness, and experience.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers' selection of technologies for use during ERT was typically driven by familiarity with available technologies as several studies reported educators refrained from adopting new technologies to support learning and teaching (Bartolic et al, 2021 ; Damşa et al, 2021 ; Müller et al, 2021 ; Väljataga et al, 2020 ). Most teachers relied on their existing digital practices, such as uploading recordings and synchronous messaging, as these had been utilised as part of their day-to-day teaching prior to emergency delivery (Bartolic et al, 2021 ; Dalipi et al, 2022 ; Damşa et al, 2021 ; Kaqinari et al, 2022 ; Oliveira et al, 2021 ). While many also expressed limited experiences with completely online delivery, the connection between existing practices and these technologies helped inform pedagogy during this time (Gao & Zhang, 2020 ; Müller et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations